2020
DOI: 10.1002/adma.202002034
|View full text |Cite
|
Sign up to set email alerts
|

Large Single‐Crystal Cu Foils with High‐Index Facets by Strain‐Engineered Anomalous Grain Growth

Abstract: The rich and complex arrangements of metal atoms in high‐index metal facets afford appealing physical and chemical properties, which attracts extensive research interest in material science for the applications in catalysis and surface chemistry. However, it is still a challenge to prepare large‐area high‐index single crystals in a controllable and cost‐efficient manner. Herein, entire commercially available decimeter‐sized polycrystalline Cu foils are successfully transformed into single crystals with a serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 29 publications
(33 reference statements)
3
51
0
Order By: Relevance
“…The high quality of the as-grown tBLG was corroborated by clear Moiré patterns in the HR-TEM and carrier mobility exceeding 68,000 cm 2 V −1 s −1 at room temperature. Our work brings inspiration for controlled growth of graphene and other 2D materials with interlayer twist, and future works still need to be done to grow tBLGs with certain twist angles, possibly by controlling the nucleation density, designing the growth substrate 48 , utilizing the axial screw dislocation 49 , 50 , or introducing intermediate layers 11 , 12 . Meanwhile, the torque toward smaller twist angles, which increases rapidly near the zero-angle, should be overcome to improve the portion of very small twist angle (near magic angle).…”
Section: Discussionmentioning
confidence: 99%
“…The high quality of the as-grown tBLG was corroborated by clear Moiré patterns in the HR-TEM and carrier mobility exceeding 68,000 cm 2 V −1 s −1 at room temperature. Our work brings inspiration for controlled growth of graphene and other 2D materials with interlayer twist, and future works still need to be done to grow tBLGs with certain twist angles, possibly by controlling the nucleation density, designing the growth substrate 48 , utilizing the axial screw dislocation 49 , 50 , or introducing intermediate layers 11 , 12 . Meanwhile, the torque toward smaller twist angles, which increases rapidly near the zero-angle, should be overcome to improve the portion of very small twist angle (near magic angle).…”
Section: Discussionmentioning
confidence: 99%
“…Such a graphene film, without any GBs and adlayers, is essential for constructing 'stacked graphene single crystals' with controlled rotation angles and number of layers by a layer-by-layer assembly method, which we will discuss later. Very recently, Wu and Li independently reported the preparation of large-area single-crystal highindex Cu surfaces [77,78]. Epitaxial growth of graphene has been reported on various indices, such as 112, 311, and 436 [77][78][79].…”
Section: Single-crystal Slg Grown From Multiple Nucleimentioning
confidence: 99%
“…Very recently, Wu and Li independently reported the preparation of large-area single-crystal highindex Cu surfaces [77,78]. Epitaxial growth of graphene has been reported on various indices, such as 112, 311, and 436 [77][78][79]. Density function theory calculations indicated that this is due to the single lowest energy state of graphene nucleation on high-index Cu surface [79].…”
Section: Single-crystal Slg Grown From Multiple Nucleimentioning
confidence: 99%
“…Recently, a technology has been developed to prepare large-area single-crystal copper foil by abnormal grain growth during the annealing of polycrystalline copper foil [14][15][16]. The abnormal grain growth is affected by multiple factors, such as driving force [17] and temperature [18][19][20]. The tension can activate the grain boundary energy of Cu foil and promote its abnormal grain growth to single crystals [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, when the surface energy as the main diving force, the abnormal grain growth trends to formation of Cu (111) with minimum surface energy [21]. When the thermal stress that arises as a result of interfacial contact as the major driving force for grain growth, abnormal grown grain with a high-index facet can be obtained [19]. High temperature (close to the metals' melting temperatures) can accelerate the abnormal grain growth [21].…”
Section: Introductionmentioning
confidence: 99%